Agronomic assessment of rice genotypes (Oryza sativa) under different levels of fertilizer application: A review - SUPRIYA; KUMAR, RAKESH; VERMA, PARKASH; CHAUDHARY, AMRESH; S, SUDARSHAN; GARG, KAMAL; PATEL, SHASHANK (The Indian Journal of Agricultural Sciences, 2024)
The current rice production system, centered around the high-input green revolution methods, tends to favour affluent farmers, leaving lower-income farmers unable to fully embrace modern agricultural techniques due to soaring input prices. In India, shrinking cultivable land and a growing population have led to intensified agronomic practices like heavy chemical fertilizer usage mainly impacting soil health and crops productivity especially rice. This trend has discouraged poorer farmers from rice cultivation due to diminishing factor productivity and profitability amidst rising input expenses, posing significant concerns about sustainability and economic viability. In this context, the review aims to assess how rice (Oryza sativa L.) genotypes perform when exposed to varying levels of fertilizer application, providing valuable insights into their adaptability and potential for increased productivity and soil fertility. It was investigated how different fertilizer levels, specifically nitrogen, phosphorus, and potassium, affects important agronomic practices, yield-related parameters, and grain quality in various rice genotypes. A diverse set of genotypes represent a broad spectrum of genetic background and adaptation strategies, including those known for their efficiency in using nutrients. Highlighting how the robustness of certain genotypes under conditions with limited nutrients maintained satisfactory yields and grain quality. In contrast, some genotypes demonstrated superior performance under higher fertility conditions, resulting in significant yield increases, larger grain sizes, and improved nutritional profiles. These approaches optimize fertilizer application, reduce the environmental impacts associated with excessive nutrient use, and ultimately enhance overall rice production.